Autoantibodies in Indian-Asians with insulin-dependent diabetes in the UK. Issue 751 (May 1988) - Odugbesan, O.; Fletcher, J. A.; Sanders, A.; Bradwell, A. R.; Botazzo, G. F.; Barnett, A. H.
Abstract : Classical insulin-dependent diabetes mellitus (IDDM) is relatively uncommon in Indian-Asians whether in India or in the UK and this may be related to immunogenetic factors. We have studied the presence or absence of islet cell antibodies and other auto-antibodies in 36 subjects with IDDM and 41 controls, all of Indian origin. Islet cell antibodies (ICA-IgG) were found in 8 subjects with IDDM but in none of the controls. Four of the 8 patients with ICA-IgG also possessed the complement fixing variety (CF-ICA). There was no definite association between possession of ICA and HLA-DR antigens. Thyroid antibodies were commoner in patients (22%) compared with controls (7%) as were parietal cell antibodies (8.3% vs 4.8%). None of the patients or controls had adrenal antibodies. The frequency of organ-specific antibodies in Indian-Asians with IDDM is similar to that of white Caucasians. The overall frequency of ICA is, however, lower than that reported for white Caucasians although the temporal distribution is similar. We conclude that even though the prevalence of IDDM in Indian-Asians is lower than in white Caucasians there is no evidence that different immunological mechanisms are involved in the pathogenesis of IDDM in the two groups.